2022
DOI: 10.3389/fimmu.2022.900273
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals interleukin-17 family members as biomarkers in the prediction for immune checkpoint inhibitor curative effect

Abstract: BackgroundThe interleukin-17 (IL-17) family contains six homologous genes, IL-17A to IL-17F. Growing evidence indicates that dysregulated IL-17 family members act as major pathogenic factors in the early and late stages of cancer development and progression. However, the prevalence and predictive value of IL-17 for immune checkpoint inhibitor (ICI) therapeutic effectiveness in multiple tumor types remain largely unknown, and the associations between its expression levels and immunotherapy-associated signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…IL-4, IL-10, and TNF-α play multifaceted roles in cancer immunity, both activating antitumor immune cells and facilitating tumor immune suppression and escape. IL-10, IL-17, and TNF-α, known for their immunosuppressive properties, promote tumor growth and are associated with poor prognoses, as corroborated by several clinical studies, whereas IL-4 is considered an enhancer of immune cell antitumor activity [41][42][43][44]. Our results showed that higher baseline levels of IL-4, IL-10, and IFN-λ, as well as elevated treatment levels of IFN-λ, TNF-α, and IL-17, were associated with improved OS.…”
Section: Discussionmentioning
confidence: 86%
“…IL-4, IL-10, and TNF-α play multifaceted roles in cancer immunity, both activating antitumor immune cells and facilitating tumor immune suppression and escape. IL-10, IL-17, and TNF-α, known for their immunosuppressive properties, promote tumor growth and are associated with poor prognoses, as corroborated by several clinical studies, whereas IL-4 is considered an enhancer of immune cell antitumor activity [41][42][43][44]. Our results showed that higher baseline levels of IL-4, IL-10, and IFN-λ, as well as elevated treatment levels of IFN-λ, TNF-α, and IL-17, were associated with improved OS.…”
Section: Discussionmentioning
confidence: 86%
“…Tumor-associated macrophages are an important part of tumor immune microenvironment ( 19 ), which are usually divided into two types, one is M1 macrophages, which are involved in inflammation and can kill cancer cells, and the other is M2 macrophage, which can promote tumor progression. Many studies have shown that, on the one hand, the abundance of macrophages in tumors is negatively correlated with the prognosis and survival of patients, and on the other hand, it is positively correlated with tumor drug resistance ( 20 , 21 ). It has been previously reported that in the early stage of tumor development, macrophages in TME are mainly M1 phenotype ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate the results of the drug sensitivity analysis, we used box plots to visualize the dispersion of IC50 values across multiple samples. Additionally, we examined the correlation between the model score and IC50 to assess the relationship between CRG expression and drug sensitivity ( 55 ). By conducting these analyses, we aimed to explore the clinical implications of CRG in gastric cancer patients, including its associations with patient characteristics and its potential role in predicting the response to common chemotherapy regimens.…”
Section: Methodsmentioning
confidence: 99%